Bisphenol A promotes breast cancer cell proliferation by driving miR-381-3p-PTTG1-dependent cell cycle progression. (April 2021) - Deng, Ping; Tan, Miduo; Zhou, Wei; Chen, Chunhai; Xi, Yu; Gao, Peng; Ma, Qinlong; Liang, Yidan; Chen, Mengyan; Tian, Li; Xie, Jia; Liu, Mengyu; et al.
Abstract: Bisphenol A (BPA) is a high-production-volume industrial chemical that facilitates the development of breast cancer. However, the molecular mechanism associated with BPA-induced breast cancer cell proliferation and migration remains elusive. In our study, we exposed MCF-7 cells to different concentrations of BPA (0.1, 1 and 10 μM) for 24, 48, or 72 h. We found that BPA exposure significantly promoted MCF-7 cell proliferation and migration but not invasion. To elucidate the mechanisms, the differentially expressed genes between the BPA and control groups were investigated with the Gene Expression Omnibus (GEO) database through GEO2R. Kyoto Encyclopedia of Genes and Genomes (KEGG) and pathway action network analyses demonstrated the important role of the cell cycle pathway in the effects of BPA exposure on MCF-7 cells. Importantly, analysis with the cytoHubba plugin of Cytoscape software coupled with analysis of enriched genes in the cell cycle pathway identified PTTG1 and CDC20 (two hub genes) as key targets associated with BPA-induced MCF-7 cell proliferation and migration. Interestingly, BPA significantly increased the protein expression levels of PTTG1 but not CDC20. Knockdown of PTTG1 inhibited the BPA-induced increase in proliferation and maintained cell cycle progression. In addition, we confirmed that the increased expression of PTTG1 upon BPA exposure was caused by miR-381-3p inhibition. Moreover, we verified that miR-381-3p expression was low and inversely correlated with PTTG1 expression in breast cancer tissues. Together, these findings demonstrate that BPA promotes high PTTG1 expression and alters the cell cycle to enhance MCF-7 cell proliferation by inhibiting miR-381-3p expression. Graphical abstract: Image 1 Highlights: BPA promotes MCF-7 cell proliferation and migration. BPA drives PTTG1-dependent cell cycle. BPA enhances PTTG1 expression by suppressing miR-381-3p expression. miR-381-3p is negatively correlated with PTTG1 level in breast cancer patients.